2019
DOI: 10.1176/appi.ajp.2018.18070849
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Executive Functioning Training Compared With Perceptual Training for Schizophrenia Spectrum Disorders: Effects on Neurophysiology, Neurocognition, and Functioning

Abstract: Cognitive remediation is an efficacious treatment for schizophrenia. However, different theoretical approaches have developed without any studies to directly compare them. This is the first study to compare the two dominant approaches to cognitive remediation (training of executive skills and training of perceptual skills) and employed the broadest assessment battery in the literature to date.Methods: Outpatients with schizophrenia spectrum disorders were randomly assigned to receive either executive training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…For individuals with more advanced stages of illness (stage 1b+), interventions targeting functional disability and neurocognitive impairment are recommended . Cognitive training has been demonstrated to improve neurocognitive performance and psychosocial functioning, with improvements in social and occupational functioning greatest when cognitive training is implemented alongside functional rehabilitation efforts …”
Section: Interventions Based On the Bmc's Youth Model Of Carementioning
confidence: 99%
“…For individuals with more advanced stages of illness (stage 1b+), interventions targeting functional disability and neurocognitive impairment are recommended . Cognitive training has been demonstrated to improve neurocognitive performance and psychosocial functioning, with improvements in social and occupational functioning greatest when cognitive training is implemented alongside functional rehabilitation efforts …”
Section: Interventions Based On the Bmc's Youth Model Of Carementioning
confidence: 99%
“…CR approaches vary widely but typically utilize computerized cognitive training as a core component. Computerized training may target lower-order perceptual abilities (Fisher et al, 2009) or higher-order executive function abilities (Best et al, 2019a; Best et al, 2019b). For a review of various approaches see Best and Bowie (2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to adding to our treatment procedures, a critical area for more work in both research and clinical environments is to examine how supplemental, continued or intermittent treatment techniques affect the durability of effects. More than sustaining immediate effects, many recent cognitive remediation studies have reported a “sleeper effect”, with larger improvements in everyday functioning in the months following treatment endpoint. As is typical with clinical trials, however, these follow‐up periods are relatively brief with respect to what we often view as lifelong issues with functioning in these disorders.…”
mentioning
confidence: 99%